Overexpression of LINC00152 correlates with poor patient survival and knockdown impairs cell proliferation in lung cancer - Shumei Feng (Nature Portfolio, 2017)
Abstract We employed RNA sequencing analysis to reveal dysregulated lncRNAs in lung cancer utilizing 461 lung adenocarcinomas and 156 normal lung tissues from 3 separate cohorts. We found that LINC00152 was highly overexpressed in lung tumors as compared to their adjacent normal tissues. Patients with high LINC00152 expression demonstrate a significantly poorer survival than those with low expression. We verified the diagnostic/prognostic potential of LINC00152 expression in an independent cohort of lung tumor tissues using quantitative RT-PCR. After knockdown of LINC00152 using siRNAs in lung cancer cell lines, both cell proliferation and colony formation were decreased. Cell fractionation and qRT-PCR analysis indicated that LINC00152 is found mainly in the cytoplasm. Treatment with Trichostatin A in cell lines having low LINC00152 expression indicated that histone acetylation may be one mechanism underlying LINC00152 overexpression in NSCLC. Western blot analyses indicated that p38a, STAT1, STAT3, CREB1, CCNE1 and c-MYC proteins were decreased after LINC00152 siRNA treatment. Our study indicates LINC00152 plays an important role in lung tumor growth and is potentially a diagnostic/prognostic marker. Further characterization of LINC00152 in regulating its target proteins may provide a novel therapeutic target of lung cancer.